Pengaruh Pengalaman dan Akuntabilitas Terhadap Kualitas Audit Internal - Usman Usman (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2019)
This study aims to determine the effect of work experience and accountability of internal auditors on the quality of internal audit. Supervision of regional government operations is carried out in stages starting from the Regency / City, Province to the Central level. The independent variables in this study are work experience and accountability. While the dependent variable in this study is the quality of internal audit. it is based on several literature studies and the results of previous studies, the results of this study indicate that work experience and accountability have a very strong role in determining the quality of internal audit, and if someone does the same work repeatedly or continuously, it will be faster and more professional in completing internal audits properly, This is because the auditor has truly understood the techniques or how to properly complete the audit and be careful in completing the audit as expected, therefore the auditor's experience and internal auditor's accountability in carrying out the audit can improve the quality of internal audit.